RANCANG BANGUN MODUL PRAKTIKUM PENGUKURAN ENERGI LISTRIK JARAK JAUH MENGGUNAKAN JARINGAN KOMUNIKASI RADIO LINK - - Azhar (Politeknik Negeri Lhokseumawe, 2014)
The data of electrical energy is periodically and continuously (in real time) necessary to examine certain quantities such voltage, real power current, reactive power, phases differences, frequency and harmonic phase both single and three phases. The application of telemetry system on electric power system measurement and monitoring of energy, especially electrical remote laboratory scale, is used to establish an integrated measurement system which has specific characteristics such as; real time reading. demand reading, reading energy and power analysis to be used not only as a laboratory instrument but can also to perform measurements of the electrical energy industry and other utilization of installations. This study is aimed to establish an integrated system of electrical energy measurement and it can be monitored in two or more remote areas. In the current concept, sensors (mobile sensing current) are installed in the target of measurement and monitoring area while the input voltage is obtained directly from the power source terminal. As the results, its were found that a voltage difference between cubicles out going and industrial process control laboratory is about 0.053% of RS voltage, 0.24% of ST voltage, and 0.053% RT voltage, whereas the difference in current increase due to the voltage drop is about 0.23% of R phase, 0.031% of S phase, and 0.031% of T phase current, in the range of radio link of 100 m